Exploring Phenolic Compounds as Quorum Sensing Inhibitors in Foodborne Bacteria - Santos, Catarina Angeli; Lima, Emília Maria França; Franco, Bernadette Dora Gombossy de Melo; Pinto, Uelinton Manoel (Frontiers in Microbiology, 2021)
The emergence of multi-drug-resistant bacteria stimulates the search for new substitutes to traditional antimicrobial agents, especially molecules with antivirulence properties such as those that interfere with quorum sensing (QS). This study aimed to evaluate the potential of phenolic compounds for QS inhibition in a QS biosensor strain (Chromobacterium violaceum) and three foodborne bacterial species (Aeromonas hydrophila, Salmonella enterica serovar Montevideo and Serratia marcescens). Initially, an in silico molecular docking study was performed to select the compounds with the greatest potential for QS inhibition, using structural variants of the CviR QS regulator of C. violaceum as target. Curcumin, capsaicin, resveratrol, gallic acid and phloridizin presented good affinity to at least four CviR structural variants. These phenolic compounds were tested for antimicrobial activity, inhibition of biofilm formation and anti-QS activity. The antimicrobial activity when combined with kanamycin was also assessed. Curcumin, capsaicin and resveratrol inhibited up to 50% of violacein production by C. violaceum. Biofilm formation was inhibited by resveratrol up to 80% in A. hydrophila, by capsaicin and curcumin up to 40% in S. Montevideo and by resveratrol and capsaicin up to 60% in S. marcescens. Curcumin completely inhibited swarming motility in S. marcescens. Additionally, curcumin and resveratrol increased the sensitivity of the tested bacteria to kanamycin. These results indicate that curcumin and resveratrol at concentrations as low as 6 μM are potential quorum sensing inhibitors besides having antimicrobial properties at higher concentrations, encouraging applications in the food and pharmaceutical industries.